An Evaluation of Sub – Chronic Toxicity of Ethanolic Extract of Cucumis trigonus Roxb. Fruit on Wistar Albino Rats - Balakrishnan, A. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTCucumis trigonus Roxb fruit is used for various ailments in Indian traditional system of medicine such as anthelmintic, liver tonic, cardio tonic, appetizer, expectorant and intellect promoting. The present study is designed to evaluate the sub – chronic toxicity of the fixed doses of ethanolic extract of Cucumis trigonus Roxb. on albino rats. Animals were treated with different fixed doses of 150,250, 350, 450 and 550 mg/kg b.w. respectively for 90 days. Body weight of the animals was noted at regular intervals, on 91st day the animals were sacrificed and the organ weights were noted. Hematological parameters like RBC, WBC, MCV, MCH, MCHC, PCV, platelets and differential counts were performed. Liver marker enzymes like AST, ALT, ACP and biochemical parameters like urea, uric acid, protein, creatinine etc., were analyzed. The liver of the animals were undergone histopathological studies to ensure the protective activity of the fruit. The results were expressed at P< 0.05 level of significance. The results prove that this extract was found to be non toxic at all the dose levels.